Homes for the Aged: a study of a Health Region in Rio Grande do Sul, Brazil - Pascotini, Fernanda dos Santos; Nazario, Camila Gomes; Rosa, Rafaela Rossini; Silva, Rosane Seeger da; Fedosse, Elenir (ABCS Health Sciences, 2020)
Introduction: With the aging of the population, the demand for Homes for the Aged (HFAs) grows. Objective: To analyze resources and population of HFAs and to check the fulfillment of the criteria from the national regulations. Methods: Descriptive quantitative study including 11 philanthropic HFAs in the state of Rio Grande do Sul, Brazil. Data was collected through a questionnaire applied to the responsible for the facility. Results: The study comprised 318 workers and 522 elders. HFAs presented: some accommodations without private bathrooms (100%); external area and administrative office (72.7%); cafeteria and support room (54.5%); ecumenical room (36.4%); rooms with more than four beds (45.5%). The prevailing reasons for admission were brought by family member (69.2%); social vulnerability (36.4%). Death was the main reason for leaving the facility. The average age of elders was 76.8 years, 58.4% were women. The dependence grade was I for 31.1%; II for 33.9%; and III for 35%. Leisure and cultural activities occurred in 72.7% of HFAs. In 27.3% there were records of visits. Only 9.1% had cooperation from families. Available human resources were nurses (72.7%); physicians and nursing assistants (63.3%); physical therapists (45.5%); psychologists (36.4%); caregivers (27.3%); occupational therapists (9.1%). In 63.3% of facilities, workers carried out mixed activities. The costs were covered by retirement pensions, partnerships, and donations. The main obstacles were financial resources or dependence on donations and rigorous health surveillance or compliance with standards. Conclusion: The HFAs partially fulfill the national criteria, impairing the quality of care provided to elders.